The Fiscal Reforms and Flat Tax in Europe and CEE Countries - Magdalena RĂDULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The aim of this paper is to realize a comparative overview of fiscal reforms and flat tax reform experiences of the new EU Member states which implemented the flat tax for fiscal policy making. In conclusion of this paper, we state that there is little evidence that the good economic performance of these countries after the reform was due to the flat tax itself: this could be attributed to wider macroeconomic recovery, better tax compliance and tax administration as a consequence of EU membership requirements.